Antifungal efficacy of herbs - Fahad M. Samadi; Shaista Suhail; Manjari Sonam; Neeta Sharma; Shruti Singh; Sushil Gupta; Ashwini Dobhal; Harsha Pradhan (Elsevier, 2019)
Candida carriage was reported to be common in oral cancer patients, with C. albicans being the predominant species. The prevalence of diseases caused by Candida species have been found to increase in recent years. Aim: The aim of our study was to find the antifungal activities at MIC of selected fifteen plant leaves extracts prepared in three different solutions (methanol and ethanol) against the opportunistic pathogen Candida albicans isolated from oral cavity infections. It may also help the clinician to treat the patient not only for the particular lesion that is present, but also to treat the infection by Candida albicans so as to reduce its potential to malignant transformation. Material n methods: Leaves extract of selected plant prepared in methanolic and eethanolic solution have been chosen for the investigation of in vitro antifungal activity which acts as expectorant and not having toxic properties on humans while for comparison or control, antifungal drugs have been taken. Results showed that Candida albicans shows most sensitivity towards the standard antibiotic cotrimoazol but very less towards other drugs like Fluconazole, minocycline, erythromycin respectively which indicated Candida albicans shows some resistance character towards drugs while the herbal extracts of Lawsonia inermis, Withania somnifer, Curcuma longa, Cymbopogon citrates and Zingiber officinale gives the best inhibitory effect and they have the potential to control growth of Candida albicans.